Plant production of Gonococcal peptide vaccine, candidate peptide display with HPVs - Lindsay, Sarah (Department of Molecular and Cell Biology, 2025)
Human Papillomavirus (HPV) and Neisseria gonorrhoeae (Ng) are prominent pathogens responsible for a significant proportion of the global burden attributed to sexually transmitted infections. While vaccines targeting HPV have seen success, an effective vaccine against gonorrhea remains elusive, as antimicrobial resistance continues to be a growing threat. This study explores the innovative approach of plant-based production for a dual vaccine against HPV16 and gonorrhea, utilizing N. benthamiana as the expression host. The vaccine design involves the incorporation of a gonorrhea peptide, mimicking the 2C7 epitope of the surface molecule LOS on gonorrhea, into the surface DE loop of HPV16 virus-like particles (VLPs). These chimeric VLPs as well as HPV16 VLPs were expressed and successfully purified from plants and demonstrated self-assembly into VLPs. The choice of N. benthamiana as the expression system is informed by its suitability for efficient and cost-effective recombinant protein production. Immunological evaluations were conducted in mice to assess the immune response elicited by the dual vaccine. The mice displayed robust antibody responses against both HPV and gonorrhea, indicating the insertion of the peptide does not disrupt the binding of antibodies to HPV16 and highlights the potential of the vaccine candidate to induce a dual protective immunity. To assess the protective efficacy of the vaccine candidate, a challenge model was developed and optimized, involving the use of HPV16 PsVs containing luciferase (FLuc). The challenge model was refined through a comparison of secreted and non-secreted reporter proteins, followed by comparison of plant and mammalian expression systems. This showed thatHPV16 PsVs containing non-secreted FLuc produced in mammalian cell culture were optimal for the challenge. Mice vaccinated with the plant-produced dual vaccine demonstrated protection against HPV infection upon challenge. In summary the chimeric and HPV16 VLP vaccine candidates were expressed in an Agrobacterium-mediated transient system in plants. The immunogenicity of the vaccine candidates was accessed in a mouse model and a further challenge model. The results demonstrated the potential of using VLPs in the display of foreign epitopes in the fight against gonorrhea and HPV. The findings contribute valuable insights into the development of vaccines against sexually transmitted infections, paving the way for innovative strategies in the field of VLP display molecules and plant molecular pharming.